A Numerical Approach to the Efficient Analysis of2D RF-MEMS Capacitor with Accelerated Motion - Shafrida, Sahrani; Mohd Shahril, Osman; Michiko, Kuroda (IEEE, 2009)
The advancement in new numerical technique is the key to success of newer generation RF MEMS devices. In this paper, a novel time-domain modeling technique that has the capability to accurately simulate the transient effect of RF MEMS variable capacitors with accelerated motion controlled by the coupling of the electrostatic and mechanical forces is presented. The relation between the sinusoidal modulations of the frequency with the acceleration is shown. Its validity has been demonstrated in comparison between the computational results of the displacement with the theoretical results. Both results are in very good agreement. The next work will be considered to include the damping coefficient. Due to its numerical efficiency, the proposed technique can be a useful technique, which makes it suitable for the numerical analysis of the moving boundary problem in the near future